Against Commodification: The University, Cognitive Capitalism and Emergent Technologies - Richard Hall; Bernd Stahl (tripleC: Communication, Capitalism & Critique)
This paper investigates how four specific emergent technologies, namely affective computing, augmented reality, cloud-based systems, and human machine symbiosis, demonstrate how technological innovation nurtured inside the University is commodified and fetishised under cognitive capitalism or immaterial labour, and how it thereby further enables capital to reproduce itself across the social factory. Marx’s critique of technologies, through their connection to nature, production, social relations and mental conceptions, and in direct relation to the labour process, demonstrates how capital utilises emergent technologies to incorporate labour further into its self-valorisation process as labour-power. The University life-world that includes research and development is a critical domain in which to site Marx's structural technological critique, and it is argued that this enables a critique of the public development and deployment of these technologies to reveal them as a fetishised force of production, in order to re-politicise activity between students, teachers and the public.